Fabrication of n-type flexible films with a double-layer structure by hybridizing Bi2Se3 and poly(vinyl alcohol). (18th July 2018) - Ohnuma, Akira
Abstract: Abstract : Here we report a new type of n -type flexible film with a double-layer structure fabricated by hybridizing an n -type inorganic thermoelectric material, bismuth selenide (Bi2 Se3 ), and an ordinary insulating polymer, poly(vinyl alcohol) (PVA). Flake-shaped Bi2 Se3 nanoparticles (Bi2 Se3 nanoflakes) modified with/without gold (Au) nanoparticles were distributed in the one side of PVA film with the particular arrangement, and the hybrid film showed a high Seebeck coefficient (−91 µV/K at room temperature) as an n -type flexible material. Our method is expected to be used for the design of flexible functional devices such as flexible thermoelectric modules.